Visitors' motivation and satisfaction at Putrajaya Asean Kelulut carnival 2016 - Sidek, Aizzah (2016)
Putrajaya Asean Kelulut Carnival (PAKC) 2016 is one of the agricultural events in Putrajaya which involve of Asean Participation. Visitors who attend to this event seemed to have different reasons, motivations and satisfaction. People still unaware about the kelulut industry. This study was carried out with the purpose to examine the motivational attributes of visitors attending an agrotourism event. A total of 120 respondents was surveyed using questionnaire in order to obtain required information for this study that included visitors socio-demographic background, motivational attributes affecting the visitor’s motivation. Descriptive analysis comprising frequencies and means were calculated. Factor analysis using principal components as the method of extraction, with oblique rotation was conducted to identify the dimensions of motivations that influence visitors in making their decision to visit the PAKC. The result shows the majority of visitors were female with majority of them belong to 16-24 years age group and most of them were full-employments workers who had a university degree education. The result shows that the visitor’s main motivation participate to PAKC are exposed to the agriculture industry in Malaysia especially about kelulut and they enjoy crowds of the carnival. This is because the most of the visitors who came to this carnival were full-time employed, they were interested in agriculture product, especially in kelulut and to release tension and give their mind and rest from a hectic lifestyle. The findings of this study will be used for the organizer of the Putrajaya Asean Kelulut Carnival to manage or improve and also to maximize the numbers of visitors attend to agrotourism events.